Kemampuan Berbunga, Tingkat Keguguran Bunga, dan Potensi Hasil Beberapa Varietas Kedelai - Suyamto Suyamto; Musalamah Musalamah (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2010)
Field experiments toidentify the flowering ability, flowering duration, percentageof flower abortion, and yield potential of several soybeanvarieties were conducted at two environments at Kendalpayak-Malang Research Station in April-July 2006 (dry season I) andGenteng-Banyuwangi Research Station (dry season II) in July-October 2006. A total of 20 soybean varieties were evaluatedby using randomized complete-blocks design with threereplications. The plot size was 0.8 m x 4.5 m with plantspacing 40 cm x 15 cm. The rate of fertilizers applied was 50kg urea, 100 kg SP36, and 75 kg KCl per ha. Plant control wasconducted intensively as recommended. Several charactersobserved were time to flower, flowering duration, number offlower, number of pod, number of filled pod, number of emptypod, seed yield/plant, and 100 seed weight. Combined analysisof variance show that all characters oberved were significantlyaffected by varieties. Flower abortion of soybean varietiesrange from a low of 6.6% for Lawit to a high of 39.1% forKawi. Lawit variety was used as high yielding potential parentwhich has lowest percentage of flower abortion (6.6%) andhighest percentage of flower to pod (93.4%).